If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying P + 2q = -1r Solving P + 2q = -1r Solving for variable 'P'. Move all terms containing P to the left, all other terms to the right. Add '-2q' to each side of the equation. P + 2q + -2q = -2q + -1r Combine like terms: 2q + -2q = 0 P + 0 = -2q + -1r P = -2q + -1r Simplifying P = -2q + -1r
| 64r^2+4=40 | | -4-6x+7x=7 | | 5t-11=t+5 | | 2x+(5x-14)=21 | | x^2+18=307 | | 4x-10+4x=22 | | y-4=-1(x+1) | | 2x-15=9x+2 | | Ln6/5 | | 5x^2-10x-7=8 | | -28=x-6x-3 | | 2/5y+6=11 | | x+28=5x+4 | | 5x+40=2x+13 | | 7-(8-3x)=20 | | 9y-6x=18 | | -6x=-76 | | -x-4=-16 | | -5-x+2x=-5 | | y-.75=0(x+3) | | 6x+30=-x+2 | | 2(4x-1)=x+7-2 | | 10-7x=-25 | | 9a-6=7a+4 | | log(x)=5.5-log(7.6) | | an=5n-10+an-1 | | ln(4n^2)=3 | | 0.09x=50 | | 4x^2+44x=153 | | 2x+(-9)=-5 | | b(x)=50-.08x | | n=83-517 |